2006
DOI: 10.1016/j.brainres.2006.07.121
|View full text |Cite
|
Sign up to set email alerts
|

Brain activation when hearing one's own and others' names

Abstract: Using functional magnetic resonance imaging, brain activation patterns were examined in response to hearing one's own first name in contrast to hearing the names of others. There are several regions in the left hemisphere that show greater activation to one's own name, including middle frontal cortex, middle and superior temporal cortex, and cuneus. These findings provide evidence that hearing one's own name has unique brain functioning activation specific to one's own name in relation to the names of others.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 34 publications
3
42
0
Order By: Relevance
“…This coactivation might mirror a general mechanism related to the detection of personally significant information. This interpretation is in line with imaging studies which have associated left frontal areas with familiarity detection (Plailly et al, 2007) and self-referential processing (e.g., hearing one's own name; Carmody and Lewis, 2006).…”
Section: Discussionsupporting
confidence: 89%
“…This coactivation might mirror a general mechanism related to the detection of personally significant information. This interpretation is in line with imaging studies which have associated left frontal areas with familiarity detection (Plailly et al, 2007) and self-referential processing (e.g., hearing one's own name; Carmody and Lewis, 2006).…”
Section: Discussionsupporting
confidence: 89%
“…Increased rTPJ activity in response to hearing one's own name has been reported previously using fMRI and PET (Carmody & Lewis, 2006;Holeckova et al, 2008;Perrin et al, 2005). The finding of diminished rTPJ activity for hearing one's own name in the ASD group is in accord with our hypothesis of a deficit in selfother distinction, and corresponds to results of earlier studies showing reduced TPJ activity in ASD during tasks requiring self-other distinction (Lombardo et al, 2011;Spengler et al, 2010) and mentalizing (Eddy, 2016;Murdaugh et al, 2014;Pantelis, Byrge, Tyszka, Adolphs, & Kennedy, 2015).…”
Section: Discussionsupporting
confidence: 82%
“…Research has shown reduced TPJ, and sometimes also mPFC activity in ASD during self-other distinction across several domains, including mentalizing (Eddy, 2016;Kennedy & Courchesne, 2008;Murdaugh, Nadendla, & Kana, 2014;Pfeifer et al, 2013;Spengler et al, 2010), adding to accumulating evidence that the TPJ is a core region implicated in ASD (Chien, Lin, Lai, Gau, & Tseng, 2015;Fishman, Keown, Lincoln, Pineda, & Müller, 2014;Kana, Uddin, Kenet, Chugani, & Müller, 2014). Importantly, the TPJ has also been found activated in the context of hearing one's own name (Carmody & Lewis, 2006;Holeckova et al, 2008;Perrin et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, we did find that the greatest activation of frontal cortex, in Brodmann areas 6 and 10, was in response to the child's own name thus providing evidence of differential neural function to her name. This activation in response to her first name is in agreement with the findings reported by Perrin et al (2005) using PET scanning as well as Carmody and Lewis (2006) using fMRI who showed evidence of differential brain activity to hearing one's own name versus others' names. Auditory self-recognition has brain activity specific to the frontal and temporal regions, as well as posterior brain regions, including the occipital cortex.…”
Section: Discussionsupporting
confidence: 92%
“…Perrin et al (2005) using EEG, as well as positron emission tomography (PET), found activation of the right medial prefrontal cortex when adults heard their own first name. Using functional magnetic resonance imaging (fMRI), Carmody and Lewis (2006) showed that adults hearing their own first name activated both the anterior regions of middle frontal cortex and superior frontal cortex, as well as posterior regions of middle and superior temporal cortex, and cuneus.…”
mentioning
confidence: 99%